EFFECT OF DIFFERENT SUCKLING PERIODS ON SOME PHYSIOLOGICAL AND PRODUETIVE CHARACTERS IN FRIESIAN HEIFERS - ALZobaydi, Abed AL-Elah Abdullah (Diyala Agricultural Sciences Journal, 2011)
The study included analyzing (60) Friesian heifers records born between (1995-1996) at AL-Lattefeia station south of Baghdad weaned within (4) different interval (70-90) , (91-110) , (111-130) and (131-150) days, to study the effect of the (4) weaning intervals on daily weight gain, weight and age at first calving ,weight and age at weaning , weight and at mating and numbers of mating . The result revealed a highly significant (P<0.01) effect of weaning intervals on weight gain which was for the first interval (70-90) days (0.49+ 0.02) kg, while the rest of the traits, weaning weight, weight and age at mating, age at the first calving and number of matting did not effected significantly by the (4) weaning intervals. The correlation coefficient between daily weight gain and both weight at weaning and age at mating was highly significant (P<0.01) (0.355) and (0.304) respectively, also there were a highly significant correlation between weight at mating with both of age at mating and age at first calving (0.341), (0.267) respectively. There were a highly significant (P<0.01) correlation between age at mating age and first calving (0.855). While the rest of the traits were not significant.